If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(x + 5) = 6 + -1x Reorder the terms: 2x(5 + x) = 6 + -1x (5 * 2x + x * 2x) = 6 + -1x (10x + 2x2) = 6 + -1x Solving 10x + 2x2 = 6 + -1x Solving for variable 'x'. Reorder the terms: -6 + 10x + x + 2x2 = 6 + -1x + -6 + x Combine like terms: 10x + x = 11x -6 + 11x + 2x2 = 6 + -1x + -6 + x Reorder the terms: -6 + 11x + 2x2 = 6 + -6 + -1x + x Combine like terms: 6 + -6 = 0 -6 + 11x + 2x2 = 0 + -1x + x -6 + 11x + 2x2 = -1x + x Combine like terms: -1x + x = 0 -6 + 11x + 2x2 = 0 Factor a trinomial. (-6 + -1x)(1 + -2x) = 0Subproblem 1
Set the factor '(-6 + -1x)' equal to zero and attempt to solve: Simplifying -6 + -1x = 0 Solving -6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 0 + 6 -1x = 0 + 6 Combine like terms: 0 + 6 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6Subproblem 2
Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5Solution
x = {-6, 0.5}
| t^3-90t=10t | | 101+27=x | | 2b^2-18=5b | | 2*81-72=90 | | p(x)=x^3-6x^2+3x-10 | | 5x-25y=4 | | 2x^2+48=20x | | 0=-(x^2+2x-63) | | x^2-52x+73=0 | | y^3+5y^2=50y | | 2n-72=90 | | (11+x)(3x)(x)=720 | | -8m-10=7m+6 | | -5v=-30 | | 5(x^2-2)=-23x | | 1.087x=50 | | 2a^2+10a+8=0 | | (6-u)(5u+4)=0 | | 1.087x=49 | | x*1.087=60 | | 91=x*7 | | log(2x-5)(x+2)=2 | | x*1.087=48 | | x*1.087=50 | | x*0.87=50 | | 2y^2+2y-2=0 | | 8x+2y=45-x | | 23b+0.25=3.20 | | -.5+.125= | | ln(x+1)+ln(x)-ln(2)=0 | | 6-6x=-6x+6 | | 10x-6=4+5x |